2010
DOI: 10.1021/la9049082
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Graphene from Graphite and Their Self-Assembly at the Oil−Water Interface

Abstract: High-quality graphene flakes have been exfoliated directly from graphite by solvothermal treatment. By introducing the oil/water interface, graphene can be easily and quickly separated from the graphene/NMP solution, which overcomes shortcomings of the time-consuming method of filtration. At the same time, the graphene film can be fabricated at the oil/water interface by controlling the volume of graphene/NMP solution. Furthermore, carbon nanotube/carbon nanospheres films can also be prepared successfully thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 15 publications
(21 reference statements)
0
57
0
Order By: Relevance
“…1c). 68 and the exfoliated synthesis of graphene from graphite 69,70 have become the most promising for the large-scale synthesis of graphene. Zhang et al 71 reported the vapour trapping growth of ower like graphene via a CVD method.…”
Section: Structure Of Graphenementioning
confidence: 99%
“…1c). 68 and the exfoliated synthesis of graphene from graphite 69,70 have become the most promising for the large-scale synthesis of graphene. Zhang et al 71 reported the vapour trapping growth of ower like graphene via a CVD method.…”
Section: Structure Of Graphenementioning
confidence: 99%
“…6,7 Intercalation-exfoliation of graphite, 8 liquid phase exfoliation or direct conversion of graphite by different routes such as ultrasonication in various solvents etc. 9,10 have also been developed. In a seminal paper in 2006, Schneipp et al 11 showed that few layer graphene sheets can be obtained by thermal splitting of graphite oxide (GO).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The advantage of interfacial assembly of low-dimensional carbon species (GR and SWCNTs) is the ability to form macroscopic films spontaneously, from self-assembly of individual flakes and particles at liquid/liquid interfaces. [22][23][24][25] There is a small body of work on the localization of chemical vapor deposited (CVD) GR and multilayer graphene (MLG) materials (consisting of a small number, between 2 and about 10 of well-defined, countable, stacked GR layers) 26 at the polarizable organic/water interface. 27,28 This approach is exemplified using the electro-deposition of Pd nanoparticles (NPs) on free-standing CVD GR 27 or MLG and SWCNT layers.…”
Section: Introductionmentioning
confidence: 99%